In Vitro Dry Matter Digestibility of Cocoa Pods Immersed in Different Alkaline Solution - R. Islamiyati (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2010)
The aim of this study was to determine in vitro dry matter digestibility (IVDMD) of cocoa pods following treatment of immersing the cocoa pods into different alkaline solution at different length of immersion time. The experiment was carried out in a 5 x 3 factorial arrangement according to completely randomized design. The replication for each treatment combination was three giving the total number of experimental units was 45. The first factor was different alkaline solutions, namely P1: water, P2: rice husk ash solution 10%, P3: coconut shell ash solution 10%, P4: cocoa pod ash solution 10% and P5: NaOH 6%. The second factor was immersion time, i.e. T1: immersion time for 8 hours, T2: immersion time for 16 hours, and T3: immersion for 24 hours. Analysis of variance indicated that alkaline solution, immersion time, and interaction between alkaline solution and immersion time affected (P<0.05) IVDMD of cocoa pods. In conclusion, the IVDMD decreased as the length of immersion time increased. Moreover, the best alkaline solution giving similar result to that NaOH 6% solution was alkaline solution made from cocoa pods ash.